Low-dose Oral Misoprostol after Cervical Ripening with a Double-balloon Catheter: 25 μg or 50 μg? Niedrig dosiertes orales Misoprostol nach Zervixreifung mit dem Doppelballonkatheter: 25 μg oder 50 μg? - Kehl, Sven; Karademir, Zeynep Selen; Weiss, Christel; Titzmann, Adriana; Schneider, Michael; Beckmann, Matthias; Bader, Simon (Geburtshilfe und Frauenheilkunde, 2025)
Purpose Misoprostol is used in low doses for the induction of labor. It is still not clear, however, which of the approved doses (25 μg or 50 μg) is more beneficial. The aim of this study was to investigate whether oral misoprostol at a dose of 25 μg or at a dose of 50 μg should be preferred to induce labor after cervical ripening with a double-balloon catheter. Material and Methods This retrospective cohort study analyzed full-term pregnancies (≥ 37 + 0 GW) in which sequential induction of labor was carried out using a double-balloon catheter followed by oral administration of misoprostol. The patients were divided into two groups: Group 1 received 50 μg misoprostol every four hours and Group 2 received 25 μg misoprostol every two hours. The primary target parameter was the rate of caesarean sections. Secondary target parameters included the interval from induction to delivery, the rate of spontaneous births, vaginal operative deliveries, and neonatal outcomes. Results 967 patients were included in the study: 514 in Group 1 and 453 in Group 2. There was no significant difference in the rate of caesarean sections between the two groups (p = 0.688). However, significantly more women in Group 2 had unsuccessful induction of labor, defined as a vaginal birth after 72 hours (15.8% vs. 8.1%, p = 0.001). But fewer neonates from Group 2 required transfer to the neonatal department (10.6% vs. 18.5%, p < 0.001). Conclusion The study found no difference in the rate of caesarean sections for the different doses of misoprostol. However the rate of vaginal deliveries only occurring after 72 hours was higher in the group treated with 25 μg misoprostol, while more neonates required transfer to the neonatal department in the group receiving 50 μg misoprostol.
CRIS-Team Scopus Importer:2025-03-14
Keywords: caesarean section; double-balloon cervical ripening catheter; induction of labor; misoprostol; neonatal outcome